Forestry Partnership Policy Between Farmer Group and Production Forest Management Unit Poigar Model - Sumual, Fandy F. B.; Mandagi, Marthinus; Kairupan, Sisca Beatrix (Technium Social Sciences Journal, 2022)
Indonesia's forests are very famous for the diversity of living plants and animals. In the forest is potency, the woods that do not can be ignored. In connection with diverse biological components, forests Provide various plants that can be utilized as providers of oxygen, materials, food, ingredients, and buildings. In a study, this approach is taken through a qualitative process. As for technique data collection used in the study, this is as follows: Method observation is something effort aware for collecting data in a manner systematic with a standardized procedure. Data analysis: the efforts carried out with working path with data, organizing data, sorting it out Becomes unit that can be managed, synthesized, searched, and found the pattern, find what is essential and what is learned as well as decide what is told to other people. Thus, the data collected from the results interview and study literature or documentation will be analyzed and interpreted to find the meaning and meaning then connected with the problem research. Collected data served in the form of narration and quoted directly from the results interview. Aspects of effectiveness policy partnership conservation forestry help the perpetrator's activity maximize results production and promotion, so that could produce quality products and promote results production to more area large so that could be known by the public wide.